Reasons Behind Germany Decision to Change Stance from Initially Against IP Waiver Policy to Agree to Waive the IP [Alasan Di Balik Keputusan Jerman untuk Mengubah Sikap dari Menentang Kebijakan IP Waiver Menjadi Menyetujui Kebijakan IP Waiver] - Roy Vincentius Pratikno; Maria Magdalena Utomo (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2023)
To equalize the distribution of the COVID-19 vaccine, South Africa, and India as representatives of the Global South submitted the proposal to the World Trade Organization. This paper through the lens of neoclassical realism aims to discuss the factors that influenced the change in German stance, which initially did not agree with IP waivers, face about to support the existence of the IP waiver policy. Neoclassical realism along with concepts such as national interests, international behavior, non-traditional security, and balance of power is used in the analysis. This research used a qualitative approach, and a descriptive method is applied, the data collection technique that the authors use is secondary data sources, and the data analysis technique that the authors use is narrative analysis. Pressure from the green parties, and NGOs and the spreading of this infectious disease have forced Germany to finally support the Intellectual Property (IP) waiver and to be implemented immediately. In addition, other external factors namely international organizations, non-governmental organizations, encouragement from other countries, and cooperation between countries play a role in the reversal of the decision. From the results of the discussion that the author has described, national interests contribute to the formation of Germany's foreign policy.Bahasa Indonesia Abstract: Untuk menyeimbangkan distribusi vaksin COVID-19, Afrika Selatan dan India sebagai perwakilan Selatan-Selatan mengumpulkan proposal kepada World Trade Organization. Artikel ini bertujuan untuk membahas faktor yang memengaruhi perubahan sikap dari Jerman, yang awalnya tidak setuju dengan kebijakan IP Waiver menjadi mendukung keberadaan kebijakan IP Waiver, dengan menggunakan kacamata Realisme Neo-Klasikal. Perspektif Realisme Neo-Klasikal ditambah serangkaian konsep seperti kepentingan nasional, perilaku internasional, keamanan non-tradisional, dan kesetaraan kekuasaan digunakan dalam analisis ini. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Selain itu, penelitian ini menggunakan sumber data sekunder sebagai teknik pengumpulan data dan analisis naratif sebagai teknik analisis data. Tekanan dari partai hijau dan NGOs serta penyebaran penyakit menular yang berbahaya ini memaksa Jerman untuk akhirnya mendukung kebijakan IP Waiver dan dapat diimplementasikan segera. Hal ini juga ditambah dengan faktor eksternal lainnya seperti organisasi internasional, organisasi non-pemerintah, dukungan dari negara lainnya, dan kerja sama antarnegara yang turut memengaruhi perubahan keputusan tersebut. Hasil dari penelitian ini menjelaskan bahwa kepentingan nasional berkontribusi terhadap kebijakan luar negeri Jerman.